You're my home - Burns, Debbie (Romance author) (Burns, Debbie (Romance author). Rescue me novel., 2023)
"Coming home will always give you a second chance... When Riley Leighton and Levi Duncan finally meet again, the chemistry between them is as hot as ever. But as much as Levi has missed Riley all these years, he still remembers the heartbreak when she left him the first time... Riley has spent a lifetime running from love. Now that she's home again, starting her dream job at the local pet rescue, she also has another chance to get it right with Levi. Everything Riley's wanted but thought she couldn't have is almost within reach. "Uplifting...brims with kindness, hope, and a stalwart belief in second chances."--